Campaign Against Violence in SMA Negeri 4 Pangkalpinang City to Strengthen Social Ethics - Zahri, Tsulis Amiruddin; Fauzi, Padlun; Prasetyo, Zanuar Barep (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The world of education faces various challenges in instilling ethical values. Many news reports in the mass media and social media present various forms of violence committed by teenagers with peers and have fatal consequences, including death. Data from the Indonesian Education Monitoring Network (JPPI) shows that there were 573 cases of violence in the school environment. Based on these figures, 40 percent were of the sexual violence type. This condition is an important concern for providing anti-sexual violence education in the educational environment. Community service was carried out in the environment of SMA Negeri 4 Pangkalpinang City, as an effort to educate teenagers to have ethics in their relationships who are already in the puberty phase. This activity involved students from the University of Bangka Belitung as messengers of anti-physical and verbal violence in the educational environment. Students have an emotional closeness and scope that is still close to the lives of high school students, so their role as messengers is very effective in providing knowledge about the importance of protecting themselves from becoming perpetrators or victims of violence in the educational environment, especially in the issue of sexual violence.